Symptoms of myocardial infarction: Concordance between paramedic and hospital records - Coventry, Linda; Bremner, A.; Williams, Teresa; Jacobs, Ian; Finn, Judith (Informa Healthcare, 2014)
Introduction: To further reduce time to definitive therapy for acute myocardial infarction (MI) patients, the focus of research needs to be on better understanding prehospital delay in recognition and response to symptoms. Paramedic clinical records can serve as a convenient source of data for such studies, but their accuracy needs to be established. Objectives: This study aimed to determine the concordance of the symptoms and symptom-onset time recorded in the paramedic patient care record (PCR) with those recorded in the hospital medical record for MI patients. Methods: A retrospective review of paramedic and hospital medical records was undertaken between January 1, 2008 and October 31, 2009 for all patients with an emergency department (ED) discharge diagnosis of MI at a single teaching hospital in Perth, Western Australia. The symptoms of MI and onset times documented in the paramedic PCR were compared with those recorded in the hospital medical record, which was considered the "gold standard." The study assessed differences in documentation using McNemar's tests, and concordance was described by kappa and adjusted kappa statistics, sensitivity, specificity, and positive and negative predictive value (PPV, NPV).Results: Of 810 patients with an ED discharge diagnosis of MI, 584 (71%) patients arrived by ambulance and 509 patients had a paramedic PCR. After exclusions, 400 patients had both paramedic PCR and hospital medical records available for review. Of 21 documented MI symptoms, the majority (71.4%) had adjusted kappa statistics greater than 0.75, and observed agreement greater than 90%. For the symptom of chest pain, sensitivity, specificity, PPV, and NPV were all over 85%. Where recorded in both records (n = 196, 49%) the symptom-onset time agreed exactly for 118 (60.2%) records, differed by 1-15 minutes for 24 (12.2%) records, and differed by 16-30 minutes for 22 (11.2%) records. Conclusion: Our study demonstrated that documentation of the common symptoms of MI and symptom-onset time was similar between the paramedic and hospital records, justifying the use of paramedic PCRs as a source of data for research in prehospital MI patient delay. Further research is required to investigate why symptom-onset time was not routinely documented for all patients with chest pain.